TANEAN LANJANG SEBAGAI STRATEGI DAKWAH ANTISIPASI KONFLIK DALAM MASYARAKAT - Achmad Nurholis Majid (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
Tanean Lanjang is a very unique culture. It’s from building construction, social interactions, and until the related spiritual values. This is reinforced by the da’wah strategy by the theologian who are accepted by everyone who runs the culture. This research aims to describe the da’wah strategy of theologian in Tanean Lanjang culture. With qualitative descriptive method, this research found that strategy of da’wah for encountering conflict conducted by theologian in Tanean Lanjang is Persuasive strategy, Al-Hikmah, Al-Mau'idzoh Hasanah. These methods are implemented within the Tanean Lanjang cultural community to motivative, facilitative, and mediative objectives.